Diabetes Mellitus and Its Therapy in Brunei Darussalam – A Critical Revisit - Najwa Hazwani, Muhammad Haskani; Long, Chiau Ming *; Dhaliwal, Jagjit Singh; Vui, Daniel Teck Wee; Goh, Bey Hing *; Ali, Majid; Shazwani, Shaharuddin; Goh, Khang Wen; Goh, Hui Poh (Dove Press, 2023)
Introduction: Diabetes is becoming an increasingly common condition across the world including Brunei Darussalam. Bruneian population, although is relatively small, represents a miniature urban community of neighbouring Southeast Asian countries as they share similar dietary and ethnicity patterns. Thus, it would be valuable to examine the findings of studies conducted among Bruneians. This study aimed to identify and review research related to the practice of patients with DM in Brunei Darussalam in order to identify associated factors influencing diabetic medication knowledge and adherence. Methods: This narrative review analyzed literature related to DM and its therapy in Brunei Darussalam. Other issues consisting of knowledge and adherence related to DM were also explored. Databases (Scopus, PubMed, and Google Scholar) were used to search literature published up to May 2022. Search terms “diabetes mellitus”, “Brunei” combined using Boolean operator were used. Results and Discussion: Conducting appropriate studies in Brunei Darussalam can benefit the government and policymakers to implement effective measures and programmes to combat the diabetes epidemic. Despite the government’s efforts, additional relevant stakeholders must be included in order to work together and engage in these initiatives in order to increase diabetes awareness, give people the power to make healthy decisions, and ultimately reduce the prevalence of diabetes in Brunei Darussalam. Patients’ medication knowledge proficiency plays a main component of ensuring appropriate and safe use of medication prescribed to them. Conclusion: Relatively poor medication knowledge and inappropriate diabetes-related practices were observed in studies conducted in Brunei Darussalam. However, no study has been done which directly measures both medication awareness and compliance among Brunei Darussalam T2DM patients. Future studies can focus on the relation between these two factors in different geographical locations of the world that are characterized by different diabetes-related practices and culture.